2022
DOI: 10.3390/ijerph192416517
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Serum Concentration Levels of Serotonin, Tryptophan and Cortisol among Stress-Resilient and Stress-Susceptible Individuals after Experiencing Traumatic Stress

Abstract: Background: Stress is a common response to many environmental adversities. However, once dysregulated, this reaction can lead to psychiatric illnesses, such as post-traumatic stress disorder (PTSD). Individuals can develop PTSD after exposure to traumatic events, severely affecting their quality of life. Nevertheless, not all individuals exposed to stress will develop psychiatric disorders, provided they show enhanced stress-resilience mechanisms that enable them to successfully adapt to stressful situations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Cortisol, which is frequently increased in individuals with IBS with chronic stress, regulates the immune system via the HPA axis 9 . The rise in cortisol levels may be linked to visceral hypersensitivity, which reflects their gastrointestinal complaints 42 . Our current findings were consistent with a recent trial that demonstrated no significant reduction in cortisol levels after 4-week of probiotic consumption 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol, which is frequently increased in individuals with IBS with chronic stress, regulates the immune system via the HPA axis 9 . The rise in cortisol levels may be linked to visceral hypersensitivity, which reflects their gastrointestinal complaints 42 . Our current findings were consistent with a recent trial that demonstrated no significant reduction in cortisol levels after 4-week of probiotic consumption 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Neurotransmitter imbalances play a crucial role in the development and progression of PTSD, as evidenced by numerous studies. Serotonin, a neurotransmitter involved in mood regulation, anxiety, and stress, has been associated with PTSD and other anxiety disorders [ 27 ]. Similarly, dysregulation in norepinephrine, a neurotransmitter involved in the body’s “fight or flight” response, has been linked to hyperarousal symptoms in PTSD [ 28 ].…”
Section: Catalytic Factors Associated With Ptsdmentioning
confidence: 99%
“…triggers fight-or-flight response to respond to stress resulting in nervous, hormonal and vascular changes that have farreaching effects (14)(15).Dopamine controls cognition, memory, attention, emotional behavior, and also controls the hypothalamic pituitary endocrine system (16). Dopamine concentration changes under chronic stress results in loss of pleasure and lack of motivation (17).Serotonin (5-HT) participates in hypothalamic control of pituitary secretion, particularly in the regulation of adreno-corticotropin hormone (ACTH) (18). Under chronic stress changes in serotonin concentration occur in many brain regions (19).…”
Section: Jmri 2023; Vol 44 No 2: (42-50)mentioning
confidence: 99%